坤中高中一年级学生平翘舌音 “z, c, s, zh, ch, sh及r”的偏误分析 - Darwis Darwis; Lily Thamrin; Lusi Lusi (Universitas Tanjungpura, 2017)
AbstractChinese Hanyu Pinyin learning is a crucial step during the Chinese language learning. Indonesian students learning Hanyu Pinyin pronunciation would be affected by the Indonesian mother tongue ,and can meet with different kinds of difficulties, especially the pronunciation of the Blade-alveolars z, c, s, and the Retro flexes zh, ch, sh, r. In view of the above, we madea survey on the Blade-alveolars z, c, s, and the Retro flexes zh, ch, sh, r,among the students from the Pontianak middle school of Indonesia. In the essay, we use the method of experimental research and statistical analysis to analyze the Chinese letter z, c, s, and zh, ch, sh, r. In the research result, the students whose mother tongue is Indonesian will be affected by their mother tongue during pronouncing the Chinese letter z, c, s, and zh, ch, sh, r. As a Chinese teacher teaching in Indonesia ,we should practice more and find more methods in the process of teaching the Hanyu Pinyin, and strengthen the using of it.And I wish the essay can help during the study of Chinse whose mother tongue is Indonesia. Keywords: Chinese initials, Blade-alveolars, Retro-flexes, Experimental research method